Prevention of antibody-mediated kidney transplant rejection - Morath, Christian; Opelz, Gerhard; Zeier, Martin; Süsal, Caner (Transplant international, 2012)
There is increasing evidence that antibody-mediated rejection is the major cause of late kidney graft failure. Prevention of antibody-mediated allograft damage has therefore become an important issue in kidney transplantation. Such prevention starts already before transplantation with the avoidance of sensitizing events. When a patient is already sensitized, precise characterization of alloantibodies and exact HLA typing of the donor at the time of transplantation are mandatory. To ensure timely and successful transplantation of highly sensitized patients, desensitization, and inclusion in special programs such as the Eurotransplant Acceptable Mismatch Program should be considered. After transplantation, close monitoring of kidney function, testing for the de novo development or changing characteristics of alloantibodies, and attention to non-adherence to immunosuppression is obligatory. In the current overview, we discuss the currently available measures for the prevention of antibody-mediated kidney graft rejection.